Culture Sustainability through Co-Curricular Learning Program: Learning Batik Cross Review - Sukadari Sukadari; Miftachul Huda (MDPI AG, 2021)
As the application of colored designs on cloth using wax in certain areas in decorating items of clothing, Batik is made through several steps that come from drawing the pattern on the paper followed by imitating the pattern on fabric, which is called ngeblat. The next phase is followed by drawing the pattern using wax, which is called mencanting. The subsequent step is the process of coloring the pattern of Batik, called pencoletan, and then subsequently followed by color-locking on Batik through covering the Batik with wax, namely basic color dyeing. This process is called menembok. The final step is making the panting process through washing, called nglorod. This process should attempt to maintain Batik with cultural sustainability, as its process contains several values, such as discipline, creativity, independence, patriotism, responsibility, cooperation, and environmental care. Based on this background, this paper attempts to examine the Batik's cultural design and to explore its sustainability through co-curricular school program activities. This study focuses on examining the potential in the process of the application of colored design through elaborating the supporting and interfering factors in a co-curricular learning program of Batik. The analysis was made through several points, namely a co-curricular learning program of Batik for enhancing cultural sustainability, a co-curricular learning program of Batik for enhancing national culture and community responsibility, and co-curricular learning of Batik for sustainability and environmental accountability.